Conceptualization and measurement of physiologic health for adults. Vol. 13, hay fever - Beck, Sjoerd; Brook, Robert H. (Robert Henry), 1943-; Lohr, Kathleen N., 1941-; Keeler, Emmett B.; Berman, Daniel M.; Goldberg, George A., 1941-; Rand eBooks (Santa Monica, CA : RAND, 1981)
Hay fever, a recurrent, noninfectious inflammation of the nasal airways, is an allergic disease commonly seen in general populations. Data on its prevalence and adverse consequences are used in the Health Insurance Study (HIS) to investigate the effect of different levels of insurance on health status and quality of care because of its widespread prevalence, impact on well-being, and potential amenability to medical treatment. This volume reviews pertinent medical literature, details the HIS definition of hay fever, describes the HIS methods for measuring its presence and impact on people's lives, presents and discusses the enrollment data from the six HIS sites, and outlines quality-of-care criteria. Illustrative findings include the following: Based on questionnaire data, 15 percent of 5,350 HIS adults currently had hay fever, and another 5 percent had it only in the past. Among the currently afflicted, 80 percent reported ill effects (mainly pain).
"July 1981."
Includes bibliographical references (p. 55-57).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Chronic diseases -- United States -- Statistics; Hay fever -- United States; Health status indicators -- United States; Health surveys -- United States; Insurance, Health -- United States -- Statistics; Chronic Disease -- Adult; Hay Fever; Health Surveys -- United States; Insurance, Health -- United States; Electronic books